Microbiological and quantitative analysis of burn wounds in the burn unit at a tertiary care hospital in Kashmir - Tahir Saleem Khan; Akram Hussain Bijli; Adil Hafeez Wani (Wolters Kluwer Medknow Publications, 2016)
Background: The burn wound represents a susceptible site for opportunistic colonization by organisms of endogenous and exogenous origin. The present study was undertaken to analyze the microflora of burn wounds of the burn patients from a tertiary care hospital in Kashmir, India. Materials sand Methods: The study included all patients with acute burns admitted from January 2010 to December 2011 (2 years). The standard techniques, as practiced during collection of microbiological specimens, were used during wound swab/biopsy collection. Results: 74.19% of swab cultures yielded single isolates. On swab culture, Pseudomonas aeruginosa was the commonly isolated organism (46.86%). Staphylococcus aureus was the most common isolate isolated during 1st postburn week (30.86%). 258/288 (89.58%) blood cultures were sterile. 8/58 (13.79%) blood cultures were positive during the second postburn week. S. aureus was the most common organism grown on blood culture (44.44%). P. aeruginosa was mostly sensitive to polymyxin B (86.0%), amikacin (40.0%), and ciprofloxacin (37.3%), respectively. S. aureus was most commonly sensitive to linezolid (85.0%) and vancomycin (78.8%%) whereas Acinetobacter spp. was sensitive to polymyxin B (65.3%), piperacillin/tazobactam (44.9%), and amikacin (38.8%). Patients (27.27%) who showed local signs of burn wound infection and positive blood culture were subjected to burn wound biopsy. 93.33% of patients who had counts >105 colony-forming unit/g of tissue showed significant association with local signs of burn wound infection and positive blood culture for any organism. Conclusion: The microbiological surveillance of burn wounds needs to be continued for a rational antibiotic policy and prevention of emergence of resistant organisms. Burn wound biopsy culture is an effective tool for quantitative analysis of burn wounds; however, subjecting this biopsy to histological examination is more predictable of burn wound infection and its correlation with burn wound sepsis.